Efferocytosis is restricted by axon guidance molecule EphA4 via ERK/Stat6/MERTK signaling following brain injury - Eman Soliman; John Leonard; Erwin Kristobal Gudenschwager Basso; Ilana Gershenson; Jing Ju; Jatia Mills; Caroline de Jager; Alexandra M. Kaloss; Mohamed Elhassanny; Daniela Pereira; Michael Chen; Xia Wang; et al. (Journal of Neuroinflammation, 2023)
Abstract Background Efferocytosis is a process that removes apoptotic cells and cellular debris. Clearance of these cells alleviates neuroinflammation, prevents the release of inflammatory molecules, and promotes the production of anti-inflammatory cytokines to help maintain tissue homeostasis. The underlying mechanisms by which this occurs in the brain after injury remain ill-defined. Methods We used GFP bone marrow chimeric knockout (KO) mice to demonstrate that the axon guidance molecule EphA4 receptor tyrosine kinase is involved in suppressing MERTK in the brain to restrict efferocytosis of resident microglia and peripheral-derived monocyte/macrophages. Results Single-cell RNAseq identified MERTK expression, the primary receptor involved in efferocytosis, on monocytes, microglia, and a subset of astrocytes in the damaged cortex following brain injury. Loss of EphA4 on infiltrating GFP-expressing immune cells improved functional outcome concomitant with enhanced efferocytosis and overall protein expression of p-MERTK, p-ERK, and p-Stat6. The percentage of GFP+ monocyte/macrophages and resident microglia engulfing NeuN+ or TUNEL+ cells was significantly higher in KO chimeric mice. Importantly, mRNA expression of Mertk and its cognate ligand Gas6 was significantly elevated in these mice compared to the wild-type. Analysis of cell-specific expression showed that p-ERK and p-Stat6 co-localized with MERTK-expressing GFP + cells in the peri-lesional area of the cortex following brain injury. Using an in vitro efferocytosis assay, co-culturing pHrodo-labeled apoptotic Jurkat cells and bone marrow (BM)-derived macrophages, we demonstrate that efferocytosis efficiency and mRNA expression of Mertk and Gas6 was enhanced in the absence of EphA4. Selective inhibitors of ERK and Stat6 attenuated this effect, confirming that EphA4 suppresses monocyte/macrophage efferocytosis via inhibition of the ERK/Stat6 pathway. Conclusions Our findings implicate the ERK/Stat6/MERTK axis as a novel regulator of apoptotic debris clearance in brain injury that is restricted by peripheral myeloid-derived EphA4 to prevent the resolution of inflammation.